Podnikanie na slovensku a hodnotenie podmienok podnikania vo vybraných regiónoch - Šúbertová, Elena (Univerzita Pardubice, 2011)
The maximum number of business entities – individuals was recorded in the Slovak Republic in the year 2008, up 418 219 enterprises. Entrepreneurs for their business are surrounded by a number of internal and external factors. These factors create a business environment. Enterprises are linked each other with mutual connections which are changing in time. Some of factors operating on business environment are sensitive on other conditions, e.g. local taxes. To 31.12.2010 were tax and non-tax revenues the state budget in the Slovak Republic with 7 962 684 737 Euros including value added tax amounted to 4 431 539 377 Euros. It is good, that all our 522 respondents feel competent to evaluate conditions for entrepreneurship in tax and insurance area and in financial support. Their evaluation in all matters was not clearly positive.
Keywords: entrepreneurship; enterprises; conditions; business environment; regions